2021
DOI: 10.1016/j.lwt.2020.110557
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale benchtop 1H NMR spectroscopy for milk analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…It is non-destructive, simple, and fast, and it can be used to perform qualitative and quantitative analysis on a variety of substances at the same time. It is now widely used in the food industry [ 15 , 16 , 17 ]. At the same time, NMR spectroscopy has been successfully used in the analysis of the composition of green coffee [ 18 ], roasted coffee [ 19 ], the effect of roasting on coffee composition [ 20 ], and coffee flavor [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is non-destructive, simple, and fast, and it can be used to perform qualitative and quantitative analysis on a variety of substances at the same time. It is now widely used in the food industry [ 15 , 16 , 17 ]. At the same time, NMR spectroscopy has been successfully used in the analysis of the composition of green coffee [ 18 ], roasted coffee [ 19 ], the effect of roasting on coffee composition [ 20 ], and coffee flavor [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Benchtop NMR spectroscopy can also be applied to the analysis of dairy products, which have been probed by time-domain NMR techniques to determine fat/moisture content and authenticity as well as to perform quality control [29]. Recently, benchtop NMR spectroscopy has been used to investigate the production conditions of lactose-free milk [26], which is produced by the lactase-catalyzed breakdown of lactose into galactose and glucose. In this case, traditional analytical techniques such as polarimetry, mid-IR spectroscopy, and high-performance liquid chromatography (HPLC) are poorly suited for the online monitoring of hydrolysis in flow mode via lactose content determination [30].…”
Section: Foodsmentioning
confidence: 99%
“…In this case, traditional analytical techniques such as polarimetry, mid-IR spectroscopy, and high-performance liquid chromatography (HPLC) are poorly suited for the online monitoring of hydrolysis in flow mode via lactose content determination [30]. Soyler et al demonstrated the applicability of benchtop NMR spectroscopy as a tool for online lactose hydrolysis monitoring in a model system for the production of lactose-free milk [26]. Milk samples were also classified based on processing type, milk source, and geographic origin.…”
Section: Foodsmentioning
confidence: 99%
“…Monakhova et al (2012) investigated the labelling accuracy of milk, lactose-free milk, and other milk derivatives (soy, oat, rice) in the markets by 1H NMR spectroscopy (Monakhova et al, 2012). Söyler et al (2021) investigated the advantages of bench-top NMR spectroscopy as a quality-control tool at different stages of milk production. First, bench-top NMR was used to monitor lactose hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…First, bench-top NMR was used to monitor lactose hydrolysis. The artificial neural network model has been developed to classify the different components of milk samples by supporting benchtop NMR spectroscopy (Söyler et al, 2021). Laref (2020) has suggested that using the bioinformatics software following 1H NMR is more advantageous for metabolite identification (Laref, 2020).…”
Section: Introductionmentioning
confidence: 99%